Effect of Pyridoxine Deficiency on Ornithine Aminotransferase in Rat Kidney and Liver - IKEDA, Masuko; OKADA, Mitsuko (Journal of Nutritional Science and Vitaminology, 1985)
The hepatic and renal activities of ornithine aminotrans-ferase (OAT) [L-ornithine 2-oxoacid aminotransferase, EC 2.6.1.13] were determined in male and female rats given diet with or without pyridoxine. OAT activities were measured in the presence of pyridoxal phosphate. Diet without pyridoxine caused a decrease in hepatic OAT activity in males and no change in females and an increase in renal OAT activity in males and a decrease in females. The increased renal OAT activity in males was associated with increased immunochemically recognizable OAT, and was due to increased synthesis of OAT as shown by measurement of [3H]leucine incorporation in vivo. Thus OAT is regulated by nutritional conditions in different ways in liver and kidney.